A young female with double mechanical prosthetic heart valves presenting with coronary embolism-a rare case report - Adhikari, Suman; Gajurel, Ratna Mani; Paudel, Chandra Mani; Devkota, Surya; Shakya, Smriti; Thapa, Shovit; Yadav, Vijay; Sharma, Manju (Journal of Advances in Internal Medicine, 2020)
Coronary embolism, though uncommon, can occur in young patients with mechanical prosthetic heart valves. Coronary embolism has been reported in patients with prosthetic heart valves with or without thrombosis in literatures. It can cause acute coronary syndrome and lead to death if threshold of diagnosis of coronary embolism is not low. Here we report a case of coronary embolism in a 26 year old female with history of double mechanical prosthetic valve replacement, presenting to our centre with acute coronary syndrome. She was managed with thrombosuction establishing almost complete revascularization.